A maintenance 3-day-per-week schedule with the single tablet regimen efavirenz/emtricitabine/tenofovir disoproxil fumarate is effective and decreases sub-clinical toxicity. (31st July 2018) - Rojas, Jhon; Blanco, Jose L.; Sanchez-Palomino, Sonsoles; Marcos, Maria A.; Guardo, Alberto C.; Gonzalez-Cordon, Ana; Lonca, Montserrat; Tricas, Amparo; Rodriguez, Ana; Romero, Anabel; Miro, Jose M.; Mallolas, Josep; et al.
Abstract : Background: Antiretroviral drugs contained in single tablet Atripla have pharmacokinetic properties that could allow for longer than once-daily dosing. We hypothesized that simplifying Atripla once daily to 3-day per week would be feasible, able to maintain viral suppression and less toxic. Methods: Virologically suppressed (≥2 years) HIV+ adults on Atripla once daily, CD4 + greater than 350 cells/μl at inclusion, and no prior documented virological failure or evidence of resistance mutations to efavirenz, tenofovir, or emtricitabine were randomized to maintain their once-daily (OD) regimen or to reduce it to 3 days (Mondays, Wednesdays, and Fridays) a week (3W) (A-TRI-WEEK pilot trial). Primary end-point was the proportion of patients free of treatment failure (noncompleter = failure) at 24 weeks. CD4 + and CD8 + cells, ultrasensitive HIV-1 RNA, Pittsburg Sleep Quality Index (PSQI), bone mineral density, plasma efavirenz levels, and fasting blood and urine chemistries were measured at baseline and 24 weeks. The study is registered at ClinicalTrials.gov, NCT01778413. Results: Sixty-one patients were randomized. All patients in both arms remained free of treatment failure (estimated difference 0%; 95% confidence interval −14.1 to 14.1). Ultrasensitive plasma HIV-1 RNA below detection threshold showed no difference between arms (70% in the 3W arm vs. 71% in the OD arm, P  = 0.933) at 24 weeks. Total cholesterol and femur T -score significantly increased, whereas PSQI, plasma efavirenz, albumin/creatinine and beta-2-microglobulin in urine significantly decreased in the 3W arm relative to OD arm. Conclusion: The A-TRI-WEEK study represents a proof of concept for the feasibility of three-day per week Atripla maintenance that should be further confirmed in a larger, well powered clinical trial.